BAY60-2770 attenuates doxorubicin-induced cardiotoxicity by decreased oxidative stress and enhanced autophagy. (1st September 2020) - Zhao, Xiao-Xiao; Cho, Haneul; Lee, Sora; Woo, Jong Shin; Song, Min-Young; Cheng, Xian Wu; Lee, Kyung Hye; Kim, Weon
Abstract: Background: Doxorubicin (DOX) administration decreases cardiac soluble guanylate cyclase (sGC) activity. We hypothesized that bypassing impaired NO-sGC-cGMP pathway resulting from the activation of oxidized and heme-free soluble guanylate cyclase (sGC) could be a therapeutic target for DOX-mediated cardiomyopathy (DOX-CM). The present study investigated the therapeutic roles and mechanism of BAY60-2770, an activator of oxidized sGC, in alleviating DOX-CM. Methods: H9c2 cardiomyocytes were pretreated with BAY60-2770 followed by DOX. Cell viability and intracellular reactive oxygen species (ROS) were subsequently measured. To determine the role BAY60-2770 in mitochondrial ROS generation and mitochondrial membrane potential, we examined mitoSOX RED and TMRE fluorescence under DOX exposure. As animal experiments, rats were orally administered with 5 mg/kg of BAY60-2770 at 1 h prior to every DOX treatment and then assessed by echocardiography and apoptotic marker and autophagy. Results: BAY60-2770 ameliorated cell viability and DOX-induced oxidative stress in H9c2 cells, which was mediated by PKG activation. Mitochondrial ROS and TMRE fluorescence were attenuated by BAY60-2770 in DOX-treated H9c2 cells. DOX-induced caspase-3 activation decreased after pretreatment with BAY60-2770 in vivo and in vitro . Echocardiography showed that BAY60-2770 significantly improved DOX-induced myocardial dysfunction. Autophagosome was increased by BAY60-2770 in vivo . Conclusions: BAY60-2770 appears to mitigate DOX-induced mitochondrial ROS, membrane potential loss, autophagy, and subsequent apoptosis, leading to protection of myocardial injury and dysfunction. These novel results highlighted the therapeutic potential of BAY60-2770 in preventing DOX-CM. Highlights: Doxorubicin directly induces oxidative stress in the mitochondria. Doxorubicin reduces cardiac soluble guanylate cyclase and reduces sGC activity. sGC pathway activation could be a therapeutic target for DOX-mediated cardiotoxicity. BAY60-2770, a sGC activator, may relieve cardiotoxicity caused by doxorubicin.